Respostas

2012-12-12T22:01:02-02:00

a primeira equaçao vai ficar assim:

                          5t+25-3t=24-t+8

                         5t+3t-8t=8+24-25

                                   -6t=7                         resposta: t é igual a 7 sobre -6

 

a segunda equaçao vai ficar assim:

                      5(x+4)+4(x-2)=3x+12

                        5x+20+4x-8=3x+12

                         5x+4x-3x=12+8-20              

                                   6x=0

                                     x=0